PROGRAMME D’ÉDUCATION BILINGUE SPÉCIAL (PEBS) AU CAMEROUN : ÉTAT DES LIEUX, OPPORTUNITÉS ET DÉFIS - Achille Fossi (Institute of Advanced Engineering and Science, 2013)
This article explores and analyzes a new initiative in bilingual education, launched at the beginning of the 2009-2010 school year in certain secondary schools in Cameroon. The Special bilingual education programme (SBEP), which is still in its beginning phase, aims essentially at training students to communicate effectively and with as little anxiety as possible in the country’s two official languages, English and French. Upon examining the various reasons for the programme and the context in which it has been implemented, existing scientific research in second language acquisition points to the conclusion that the success of this most relevant programme would eventually lead to a complete remodelling of the French-English bilingual education system in Cameroon.DOI: http://dx.doi.org/10.11591/ijere.v2i4.2929